(5x+4)+(x-8)-(3x+4)=

Simple and best practice solution for (5x+4)+(x-8)-(3x+4)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (5x+4)+(x-8)-(3x+4)= equation:


Simplifying
(5x + 4) + (x + -8) + -1(3x + 4) = 0

Reorder the terms:
(4 + 5x) + (x + -8) + -1(3x + 4) = 0

Remove parenthesis around (4 + 5x)
4 + 5x + (x + -8) + -1(3x + 4) = 0

Reorder the terms:
4 + 5x + (-8 + x) + -1(3x + 4) = 0

Remove parenthesis around (-8 + x)
4 + 5x + -8 + x + -1(3x + 4) = 0

Reorder the terms:
4 + 5x + -8 + x + -1(4 + 3x) = 0
4 + 5x + -8 + x + (4 * -1 + 3x * -1) = 0
4 + 5x + -8 + x + (-4 + -3x) = 0

Reorder the terms:
4 + -8 + -4 + 5x + x + -3x = 0

Combine like terms: 4 + -8 = -4
-4 + -4 + 5x + x + -3x = 0

Combine like terms: -4 + -4 = -8
-8 + 5x + x + -3x = 0

Combine like terms: 5x + x = 6x
-8 + 6x + -3x = 0

Combine like terms: 6x + -3x = 3x
-8 + 3x = 0

Solving
-8 + 3x = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '8' to each side of the equation.
-8 + 8 + 3x = 0 + 8

Combine like terms: -8 + 8 = 0
0 + 3x = 0 + 8
3x = 0 + 8

Combine like terms: 0 + 8 = 8
3x = 8

Divide each side by '3'.
x = 2.666666667

Simplifying
x = 2.666666667

See similar equations:

| n*5=55 | | 5x+18=9x-2 | | x^2-1=3x+3 | | -5(5x-1)=-145 | | 5z-z+11=43 | | 4(2x-7)=5(4x+8) | | 7(6+10x)=462 | | 7(1+4x)=259 | | 7x-20=x+22 | | 3(4x-2)=5(2x+6) | | -8+10+12=24 | | 2(-1x+5)=-10 | | 8x^2-4x+4=11 | | x^2-3x+11=2x+5 | | 3x+4=-8+4x | | (2X-1)2=0 | | 5y+y-4=20 | | x+4=-7x-60 | | x^2+11x+17=4x+5 | | Y+10=1 | | (3.36*78+4x)/(78+x)=3.5 | | 5(4x+2)=3(2x-6) | | 6+6x=-7x+58 | | 6+6x=-7x-58 | | 6(2x-3)=2(x-4) | | x^2+7x+5=3x+2 | | 2(3x+4)=5(x+5) | | -2x-6=2-4x(x-1) | | 9v^6-15v^3/3v^3 | | 5*7+2y=10 | | 6+6x=-7x-60 | | 5(3x+4)=2(x+12) |

Equations solver categories